EFFECT OF SOAKING WITH ATONIC, WATER HYACINTHS COMPOST AND BIOFERTILIZERS ON VEGETATIVE AND FLOWERING GROWTH OF TUBEROSE - Z. H. ALI,; S. A. Abdul-Latif, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate effect of soaking Polianthes tuberosa L. bulbs in Atonic solution and inoculation with Stenotrophomonas maltophilia and Glomus mosseae, and fertilizing with two levels (3% and 4%) of water hyacinths  Compost on some vegetative and floral growth characters of the Peral variety of tuberose plants in a Factorial experiment during spring season of 2022 using a randomized completely block design with three replicates. Tuberose bulbs were planted in black plastic bags containing 6 kg of a sandy loam soil. The results of the three-way interaction showed that the treatment of soaking with Atonic, inoculation with the combination of the biofertilizer, and fertilization with 4% level of water hyacinths Compost significantly outperformed other treatments in plant height, number of inflorescences, dry weight of flowers, vase life, and aromatic oil concentration with values of 47.33 cm, 55.33 inflorescences plant-1, 5.78 grams, 16 days,and 0.71% respectively, compared to the control treatment which resulted in values of 21.67 cm, 5.67 inflorescences plant-1, 1.81 grams, 8 days,and 0.42% respectively.